Assesment of Plastic Waste on Agricultural Land in Kashambya Sub-County Rukiga District. - Hazaara, Annah (Kabale University, 2024)
The main objective of the study was to assess the community's perception of plastic dumping on agricultural land in the Kashabya Sub-county. The study employed a purposive sampling technique to select the 40 farmers to participate in the study. Semi-structured questionnaires were used to collect the data and analyzed using SPSS version 25, descriptive statistical analyses on the study variables to generate frequencies, tables, and graphs for the interpretation of the data. Results show that most respondents were youths aged between 25-34 years (33%) and 18-24 years (28%) and most were married at 55%. In terms of gender, 51% of the respondents were males and 49% were females. The majority of the respondents hand attained the secondary level of education (35%) and University level (33%). The household size was 1-3 (10%),4-6 (53%), 7-9 (25%),10-12 (10%) and above 12(2%). The study shows that most of the respondents had access to agricultural land at 80% but most of them had small land of 2-5 acres (45%), 0-1(17%). 6-9(18%), 10-13(5%), and above 18 (2%) Most of the farmers used plastics on their farm (77%), and used mainly plastic containers (48%) and polythene bags (45%). Of the plastics used, 70% of them were dumped in the farms by the farmers and 30% were not. The most dumped ones were plastic bottles (65%), polythene bags (57%), old jerrycans (35%), old sacks (10%), sachets of seeds (25%), and used syringes (3%). The dumping of the plastics could be attributed to inadequate and or lack of proper dumping sites (63%). The farmers who did not dump plastics on the farms opted for the use of the rubbish pit (60%), recycling/re-using and reselling, (35%), while the rest were fond of littering the plastic waste, (5%). It was observed that farmers had to some extent put in place some measures to reduce the littering of farmland with plastic waste, including burning, public sensitization, and recycling. However, it was necessary to institute strong environmental management bylaws and mechanisms for enforcing compliance.